2023
DOI: 10.1186/s13075-023-03009-7
|View full text |Cite
|
Sign up to set email alerts
|

Geo-epidemiology of autoantibodies in rheumatoid arthritis: comparison between four ethnically diverse populations

Abstract: Background Rheumatoid arthritis (RA) occurs across the globe in different ethnic populations. Most RA patients harbor anti-modified protein antibodies (AMPA); however, it is unclear whether differences exist in autoantibody responses at different geographic locations and between different ethnic groups, which could provide new clues regarding factors underlying autoantibody development. We therefore investigated AMPA prevalence and association with HLA DRB1 alleles and smoking in four ethnicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Therefore, only the IgG isotype was considered for meta-analysis. Five publications included a patient collection; the remaining publication contained four patient sets, each from a different continent [ 5 ]. Therefore, we considered nine patient sets from previous studies and the two collections reported here.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, only the IgG isotype was considered for meta-analysis. Five publications included a patient collection; the remaining publication contained four patient sets, each from a different continent [ 5 ]. Therefore, we considered nine patient sets from previous studies and the two collections reported here.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the bibliography of these publications did not reveal any additional sources. One of the publications was a meeting abstract at the time of the search [ 33 ], but the full article became available before the final analyses [ 5 ]. This article includes four patient sets that join the five previously published studies and our two RA collections.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations